2013
DOI: 10.1111/ajes.12036
|View full text |Cite
|
Sign up to set email alerts
|

Financialization and Income Inequality in the United States, 1967–2010

Abstract: This article presents a historical overview of the late 20th‐century advent of financialization, that is, the unprecedented growth of the financial sector. We summarize its origins and consequences, particularly greater income inequality. An econometric model quantifies the relationship. We conclude that along with higher unemployment and an eroding minimum wage, the growth of the U.S. financial sector has contributed to the exacerbation of inequality in recent decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 14 publications
2
39
0
1
Order By: Relevance
“…This results is corroborated by his later study where, using dividend and interest payments of non-financial corporations to represent financialization and employing a time-series cross-sectional dataset of 13 countries over the time period from 1986 until 2007, he found support for the existence of a relationship between increasing dividend and interest payments of nonfinancial corporations and the decline of the share of wages in national income Dünhaupt (2016). These results found support from similar studies (Hein, 2015;Stockhammer, 2012;Van Arnum & Naples, 2013). While Hein (2015) and Stockhammer (2012) employed the shift in the financial sector share in the economy and the increase in management salaries and rising profit claims of the rentiers to capture financialization, and Van Arnum & Naples (2013) made use of the relative share of financial sector in GDP, all of them found that financialization has contributed to the falling labor income share and income inequality since the early 1980s.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…This results is corroborated by his later study where, using dividend and interest payments of non-financial corporations to represent financialization and employing a time-series cross-sectional dataset of 13 countries over the time period from 1986 until 2007, he found support for the existence of a relationship between increasing dividend and interest payments of nonfinancial corporations and the decline of the share of wages in national income Dünhaupt (2016). These results found support from similar studies (Hein, 2015;Stockhammer, 2012;Van Arnum & Naples, 2013). While Hein (2015) and Stockhammer (2012) employed the shift in the financial sector share in the economy and the increase in management salaries and rising profit claims of the rentiers to capture financialization, and Van Arnum & Naples (2013) made use of the relative share of financial sector in GDP, all of them found that financialization has contributed to the falling labor income share and income inequality since the early 1980s.…”
Section: Introductionsupporting
confidence: 64%
“…The finding suggests that the higher the university participation rate the higher the income inequality level. This goes with the common wisdom and supports Van Arnum & Naples (2013). The college participation rate in this study employs the data of the university participation rate of the population between the age of 18 and 24 years.…”
Section: Social Conditions and Income Inequalitymentioning
confidence: 62%
See 3 more Smart Citations